PHP Web 2.0 mashup projects : create practical mashups in PHP, grabbing and mixing data from Google Maps, Flickr, Amazon, YouTube, MSN Search, Yahoo!, Last.fm, and 411Sync.com /: create practical mashups in PHP, grabbing and mixing data from Google Maps, Flickr, Amazon, YouTube, MSN Search, Yahoo!, Last.fm, and 411Sync.com. (2007) - Unknown
No abstract available